(untitled) (Journal of Engineering, 2023)
Cowpea is a very important legume in Nigeria that is being utilized to Substitute high-cost animal protein for low-income people. The knowledge of some physical properties of various moisture contents is of utmost importance in the design of its handling and processing equipment and machinery, which is the aim of this work, which studied the physical properties of IT99K-573-1-1 (SAMPEA14) variety of Cowpea within 8.77 to 21.58 % db moisture content. The properties studied include Major, Intermediate, and Minor diameters, Sphericity, Surface area, Specific gravity, Volume, Bulk density, 50-tap density, 100-tap density, 1250-tap density, seed mass, Angle of repose, Geometric mean diameter, and Arithmetic mean diameter. The obtained results indicate that the Size, Sphericity, Geometric, Arithmetic diameter, Surface area, and seed mass increase linearly with an increase in moisture content by 13.8%, 27.4%, and 16.1% for the size, respectively. While sphericity rises by 7.5% and geometric mean diameter, arithmetic mean diameter, surface area, and grain mass increase by 22.2%, 20.7%, 24.9%, and 16.11%, respectively. Specific gravity, density, and repose angle were inversely linearly related to moisture content. Regression equations for each of the properties related to the grains’ moisture content were developed.